Farm to market Empowering small-scale farmers through value-generative architecture of an agro-industrial food hub in Candelaria, Quezon - Seville, Cheaster Marie Lorono; Gines, Leonido Jr. M. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
Agricultural productivity faces numerous challenges, including limited market access,
inadequate infrastructure, poor storage, and substantial postharvest losses. Centralized food
hubs offer a potential solution by aggregating produce, connecting farmers to markets, and
providing processing/packaging facilities. However, research on their blueprint,
environmental impact, and sustainability is limited. This study aimed to fill the gaps in
existing projects in modernizing and collaborating traditional spaces, agricultural activities,
and facilities by designing a model of a centralized food hub that optimized agricultural
productivity, addressing economic, social, and environmental concerns. The goal of designing
a centralized food hub in Candelaria is achieved by developing strategies to promote the
proposed model's adoption and scalability for rural agricultural development. To achieve the
objective, the researcher used highly adaptable low-technologies in the design, and design
strategies that will aid in the sustainability of the development. The study initially reviewed
academic articles, journals, and code reviews to find the gaps in the existing model of food
hubs, and proceeded to use interviews and focus group discussions with farmers and
individuals in the agriculture industry to gather relevant information and data on existing
practices and gaps. Based on the findings, a specific design approach of Value-Generative
Design was applied and focused on 1) sustainability for agricultural productivity and its
replicability into practice; 2) functionality of enhanced market access; and 3) business
development support for farmers. The research aimed to add value to the agricultural sector
by designing a sustainable model of an Agro-Industrial Food Hub in Candelaria, Quezon.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Food sustainability -- Candelaria (Quezon); Food supply -- Candelaria (Quezon)